2021
DOI: 10.1007/s00384-021-04030-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus transanal total mesorectal excision in sexual, anorectal, and urinary function: a multicenter, prospective, observational study

Abstract: Purpose Improved long-term survival after low anterior resection (LAR) for rectal cancer highlights the importance of functional outcome. Urogenital and anorectal dysfunction is frequently reported after conventional LAR. Advanced minimally invasive techniques such as robotic (RoTME) and transanal total mesorectal excision (TaTME) might improve functional results by precisely dissecting and preserving autonomic nerves. We compared functional outcomes after RoTME or TaTME in a multicenter study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 42 publications
(99 reference statements)
0
24
1
Order By: Relevance
“…Since then, there has been a lot more data on both short-and moderate-term oncological outcomes which suggests that TaTME is as safe as laparoscopic TME and other approaches [26][27][28] (Table 1 [21,26,[29][30][31]). Roodbeen et al [32] for instance reported a local recurrence rate of only 3% in their 2021 multicenter observational study of 767 patients.…”
Section: Oncological Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, there has been a lot more data on both short-and moderate-term oncological outcomes which suggests that TaTME is as safe as laparoscopic TME and other approaches [26][27][28] (Table 1 [21,26,[29][30][31]). Roodbeen et al [32] for instance reported a local recurrence rate of only 3% in their 2021 multicenter observational study of 767 patients.…”
Section: Oncological Resultsmentioning
confidence: 99%
“…A multicenter prospective observational study comparing 55 robotic TME and 65 TaTME also reported similar sexual functions in both groups. The robotic group however reported slightly better anorectal function with the TaTME group superior in terms of preserving male urinary function [ 29 ]. The dearth of high-level evidence and limited studies makes it challenging to comment on the functional results of TaTME and we have to await further high-quality evidence such as the ongoing COLOR-III trial to shed more light on this issue [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter observational study [29] reported that the robotic approach could be superior in preserving post-operative anorectal function comparing TaTME, even though this result may be in uenced by the consistent difference in the proportion of patients who underwent NAD among the groups used for comparison of data.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have attempted to demonstrate the efficacies of taTME compared to laparoscopic and/or robotic TME, but convincing results have not yet been obtained (Table 1). 44,[47][48][49][50][51] Even international expert consensus has had difficulty reaching agreement on the indications for or best practice of taTME. 29 Most of the favorable results of taTME have been reported from large referral centers with highly skilled colorectal surgeons.…”
Section: Cost-effectiveness Of Tatmementioning
confidence: 99%